Dynamic Algorithmic Impact Assessment to Promote an Ethical Use of AI in Businesses - Mbuy, Shefeh Prisilia (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
My PhD research focus is to produce a critical review of literature in Algorithmic Impact Assessment (AIA) and to develop an AIA tool that can be used to evaluate potential unintended impact of AI systems.